DEVELOPMENT OF SORPTION MATERIALS OF WIDE FUNCTIONAL PURPOSE IN THE V.I. VERNADSKII INSTITUTE OF GENERAL AND INORGANIC CHEMISTRY OF THE NAS OF UKRAINE - Maltseva, Tetiana; Dzyazko, Yulliya (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2023)
The review is devoted to the work, which were performed at the V.I. Vernadskii Institute of General and Inorganic Chemistry of the NAS of Ukraine according to the direction of the development of sorption naterials of wide functional purpose. All sorbents can be used in separation processes: due to their coarse dispersion and mechanical strength, they can be used as fillers for sorption columns.The direction of early works is the development of amorphous hydrophosphates and double hydrated oxides of multivalent metals, intended for the removal of toxic inorganic ions from water (arsenate-, chromate- and borate-anions, Cu2+, Pb2+, Cd2+cations etc.). Currently, attention is focused on the development of composite materials.The base of inorganic composites is hydrophosphate and oxide sorbents, and the modifiers are the advanced carbon materials, lithium-titanium and lithium-titanium-manganese spinels etc.Sorbents based on ion-exchange resins modified with inorganic ionites have also been developed.The combination of various components in composites makes it possible to obtain sorbents with improved properties (faster sorption, increased capacity and selectivity, sorption capacity in a wider pH range, easier regeneration) or multifunctional materials that sorb both inorganic and organic compounds, for example, pesticides. Prospective field of research is the development of technologies that include not only the extraction of toxic and valuable components from liquids of natural, technological and biogenic origin, but also the regeneration of the sorbent and processing of the concentrate to obtain commercial products.Thus, the integration of lithium sorption concentration into the process of reverse osmosis water desalination has been proposed. The processing of the solution formed during the regeneration of the sorbent includes the production of lithium carbonate and a complex fertilizer for acidic soils. Composites, the components of which are natural materials, are also in the focus of attention.Magnetic sorbents based on biopolymers, proposed for extraction of oil and oil products from water surfaces. Composites based on zeolites are used as containers for liquid fertilizers Another direction of research is the creation of composites - potential membrane modifiers for separation processes.